Effects of Agro-Waste and Bio-Particulate Fillers on Mechanical and Wear Properties of Sisal Fibre Based Polymer Composites. (2017) - Kumar, Sandeep; Kumar, Yogesh; Gangil, Brijesh; Kumar Patel, Vinay
Abstract: In this study, the effects of mustard cake and pine needle on tensile strength, impact energy and abrasion of sisal fibre based polymer composites were investigated. Here nine different samples were prepared by reinforcing varied sisal fibres of 20, 30 and 40 wt% in polyester matrix and hybridizing these with natural pine needles, and agro-waste mustard cakes at a fixed quantity of 5 wt% each for tailoring the mechanical and wear properties. The hybridization of both mustard cake and pine needles enhanced the mechanical and wear properties of Sisal-based polyester composites with better results obtained with pine needles fillers than those of mustard cakes. The hybrid polymer composites based on 40 wt% Sisal and 5 wt% pine needles delivered superior mechanical and wear properties among all. From these observations, it can be clearly demonstrated that the natural fillers and/or agro-waste could be futuristic viable alternatives of commercial particles toward development of eco-friendly; renewable and light weight natural fibres based polymer composites comprising high mechanical properties and wear resistance.